Caffeine and anaerobic performance: Ergogenic value and mechanisms of action - Davis, J. K.; Green. J. M. (Sports Medicine, 2009)
The effect caffeine elicits on endurance performance is well founded. However, comparatively less research has been conducted on the ergogenic potential of anaerobic performance. Some studies showing no effect of caffeine on performance used untrained subjects and designs often not conducive to observing an ergogenic effect. Recent studies incorporating trained subjects and paradigms specific to intermittent sports activity support the notion that caffeine is ergogenic to an extent with anaerobic exercise. Caffeine seems highly ergogenic for speed endurance exercise ranging in duration from 60 to 180 seconds. However, other traditional models examining power output (i.e. 30-second Wingate test) have shown minimal effect of caffeine on performance. Conversely, studies employing sport-specific methodologies (i.e. hockey, rugby, soccer) with shorter duration (i.e. 4-6 seconds) show caffeine to be ergogenic during high-intensity intermittent exercise. Recent studies show caffeine affects isometric maximal force and offers introductory evidence for enhanced muscle endurance for lower body musculature. However, isokinetic peak torque, one-repetition maximum and muscular endurance for upper body musculature are less clear. Since relatively few studies exist with resistance training, a definite conclusion cannot be reached on the extent caffeine affects performance.